2018
DOI: 10.1002/hlca.201800014
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Oligodithienothiophenes: Transmembrane Anion Transport Along Chalcogen‐Bonding Cascades

Abstract: The design, synthesis, and evaluation of multifunctional dithieno[3,2‐b;2′,3′‐d]thiophene (DTT) trimers is described. Twisted push‐push‐pull or donor‐donor‐acceptor (DDA) trimers composed of one DTT acceptor and two DTT donors show strong mechanochromism in lipid bilayer membranes. Red shifts in excitation rather than emission and fluorescence recovery with increasing membrane order are consistent with planarization of the twisted, extra‐long mechanophores in the ground state. The complementary pull‐pull‐pull … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 88 publications
2
41
0
1
Order By: Relevance
“…This choice was made to benefit from much experience with aldehyde library screening, and to avoid complications from product purification in the presence of different, unprotected boronic acids . The twisted push‐pull scaffold in flippers was synthesized from tetrabromothiophene 13 following recently developed procedures ( Scheme ) . Without going into details, an elegant condensation of 13 with acetaldehyde 14 and thiol 15 to afford the DTT core 16 was adapted to flipper synthesis because the emerging significance of the probe called for a more cost effective preparation.…”
Section: Resultsmentioning
confidence: 99%
“…This choice was made to benefit from much experience with aldehyde library screening, and to avoid complications from product purification in the presence of different, unprotected boronic acids . The twisted push‐pull scaffold in flippers was synthesized from tetrabromothiophene 13 following recently developed procedures ( Scheme ) . Without going into details, an elegant condensation of 13 with acetaldehyde 14 and thiol 15 to afford the DTT core 16 was adapted to flipper synthesis because the emerging significance of the probe called for a more cost effective preparation.…”
Section: Resultsmentioning
confidence: 99%
“…In the following, we answer the question which regioisomer is preferentially formed, show that fast intramolecular rearrangements influence the result, explain why this detailed question is of general interest, and apply the lessons learned to 3-alkyl-1,2diselenolanes. Recent progress with chalcogen bonding research [23] [24] confirmed that this shift of attention from sulfur to selenium is not a simple extension. Because of the longer SeÀ Se and SeÀ C bonds, ring tension from lone pair repulsion and losses of hyperconjugation are less pronounced in 1,2-diselenolanes than in 1,2-dithiolanes.…”
mentioning
confidence: 99%
“…They have been studied extensively in crystal engineering and for intramolecular conformational control in solution, including prominent use in medicinal chemistry and pioneering applications in covalent catalysis . The use of intermolecular chalcogen bonds in functional systems in solution is rare and recent, non‐covalent chalcogen‐bonding catalysis has been introduced only last year. [ ][ ][ ] The key to success was the idea that the somewhat awkwardly ‘hidden’ position of the σ holes on the side of chalcogen‐bond donors turns into an advantage as soon as transition‐state recognition in the focal point of two adjacent donors is considered .…”
Section: Methodsmentioning
confidence: 99%